Clinical phenotypes of psychosis and reoffending risk among justice-involved adolescents: a population-based cohort study - Akpanekpo, Emaediong I.; Butler, Tony (Frontiers in Psychiatry, 2025)
BackgroundHigh reoffending rates among justice-involved adolescents necessitate identifying modifiable risk factors. Given the elevated prevalence of psychosis in this group compared to the general adolescent population, determining its contribution requires differentiation by clinical phenotypes and quantification of associated risk. This study aimed to determine the association between clinical phenotypes of psychosis and reoffending among justice-involved adolescents.MethodWe conducted a retrospective cohort study using linked administrative health and justice data (2001-2021) from New South Wales, Australia. Justice-involved adolescents (10–17 years) with a diagnosed psychotic disorder identified from hospital/emergency records (n=236) were matched (approx. 1:3) on age, sex, and index offense year to controls without psychosis (n=679). Time to first general and violent reoffending conviction within 24 months was analyzed using stratified Cox proportional hazards models, adjusting for confounders.ResultsCompared to controls, schizophrenia-related psychosis was significantly associated with increased hazards of general reoffending (adjusted Hazard Ratio [aHR]=1.51, 95% CI: 1.10–2.07) and violent reoffending (aHR=2.71, 95% CI: 1.87–3.94). Substance-induced psychosis also showed significantly increased hazards for general reoffending (aHR=3.09, 95% CI: 1.73–5.50) and violent reoffending (aHR=2.87, 95% CI: 1.49–5.56).ConclusionsNon-affective psychoses significantly elevate reoffending risk among justice-involved adolescents, with different magnitudes of risk associated with schizophrenia-related and substance-induced psychosis. Findings highlight the need for nuanced risk assessment and targeted strategies, including routine screening, early intervention, and integrated care pathways within the youth justice system.